ruta turística cultural del cantón Calvas de la provincia de Loja - Bravo Valarezo, Fernando Rafael (2016)
South of our Ecuador is the border province of Loja, formed by a number of valleys that provides residents land fertile ideal for agriculture and livestock, one of the 16 cantons that are part of this province is the canton of Calvas, birthplace of men warriors guardians of the homeland, a land in constant development due to its commercial activity with the neighbouring brethren of the Peru. This thesis that bears the name of CULTURAL tourist route of the CANTON bald spots of the province of LOJA, is aimed to contribute to the tourist development of the canton, through the consolidation of this work. The canton of Calvas has a large tourist heritage reason by which started with the diagnosis of the current situation of the place through the literature review for the knowledge of concepts and necessary field where detail the geographical, historical, social, cultural and tourist aspect to know the exact location of each of the attractions of the canton and deepen the studies on them. Established objectives and methodologies in order to effectively achieve compliance with the present research work for which the General objective is based on the construction of the "tourist route of the bald spots of the province of Loja canton", achieving thus give to discover, disseminate and promote the route to the inhabitants of the place. For the fulfilment of the same was raised the following specific objectives: "Make tourism diagnosis of the current situation of the bald spots of the province of Loja canton", where data collection, was made by means of the thesis work, books, interviews and direct observation gathering necessary information that facilitated developing the matrix of Carla Ricaurte, records of inventory and ranking of the Ministry of tourism of the Ecuador , and tab overview which specifies synthesized information on the appeal, which allowed to determine the lack of knowledge of the attractions by its inhabitants. For the fulfilment of the second objective, "Propose the design of the tourist route to the authorities of the canton Municipal GAD bald", delved into the information collected in the matrix of Carla Ricaurte and chips of inventory and this way the most important tourist attractions of the place was selected to form part of the Cultural tourist route , which has stops for both specific power as to make photographs, tourist maps of the canton, and the Cultural tourist route, was developed at the same time in the same way was prepared a script of the route for easy interpretation. They worked with methods such as: deductive which helped to verify the information obtained, the synthetic and analytical which served to determine changes, strategies and potential solutions to the problems encountered in the development of the work, we also used the technique of the interview where the community was interested in being part of this route. 5 To comply with the third goal, "Socializing the proposal of the route tourist to the authorities competent", was prescribed the technique of MARPP, which was carried out through the participatory workshop attended by representatives from tourism-related establishments and thus meet their different criteria and recommendations around the Cultural tourist route which allowed to establish some strategies to improve and strengthen the content of the route. The contribution of this research is to highlight the tourism potential of the canton of Calvas, through the implementation of the Cultural tourist route, which unveils attractions of great interest such as the Cerro Jacala which attracts the attention of both national and foreign tourists to practice adventure sports like trekking and rock climbing It is of vital importance to give greater enhancement to the present route by directing it to conservation and his presence at the time, providing the information on this and other activities that take place in the canton. Therefore it has come to the conclusions that the canton lacks tourist projects, tourist routes, tourist information centers, which has led to low quality tourist infrastructure, similarly identified little interest from the community and tourist establishments in being part of any tourism development initiatives. Recommendations that arise at the end of this investigative work are targeted to the establishments of tourist services of the canton, to carry out the necessary actions for the dissemination of the attractions, offering alternatives to the tourists visiting new places and different tourist activities to the already customary in the city. The cantonal GAD of bald spots so that it takes into account this research as a contribution to the tourist development of the sector.